Per què un assaonador català afirmava a mitjans del segle XVII que era entès en «istorias? - TARRÉS, ANTONI SIMON I. (Scripta, 2023)
Based on the assertion that the seasoner Miquel Parets makes in his diary of selfconsideration understood in «istòrias», the causes and ways of expanding the knowledge of historical discourse in the Catalan society of the Baroque are explored. It is noted that, with respect to the previous century, the most relevant changes occurred in the field of consumption and dissemination.